New antibiotics for bad bugs: where are we? - Bassetti, Matteo (BioMed Central, 2013)
Bacterial resistance to antibiotics is growing up day by day in both community and hospital setting, with a significant impact on the mortality and morbidity rates and the financial burden that is associated. In the last two decades multi drug resistant microorganisms (both hospital- and community-acquired) challenged the scientific groups into developing new antimicrobial compounds that can provide safety in use according to the new regulation, good efficacy patterns, and low resistance profile. In this review we made an evaluation of present data regarding the new classes and the new molecules from already existing classes of antibiotics and the ongoing trends in antimicrobial development. Infectious Diseases Society of America (IDSA) supported a proGram, called “the ′10 × ´20′ initiative”, to develop ten new systemic antibacterial drugs within 2020. The microorganisms mainly involved in the resistance process, so called the ESKAPE pathogens (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumanii, Pseudomonas aeruginosa, and enterobacteriaceae) were the main targets. In the era of antimicrobial resistance the new antimicrobial agents like fifth generation cephalosporins, carbapenems, monobactams, β-lactamases inhibitors, aminoglycosides, quinolones, oxazolidones, glycopeptides, and tetracyclines active against Gram-positive pathogens, like vancomycin-resistant S. aureus (VRSA) and MRSA, penicillin-resistant streptococci, and vancomycin resistant Enterococcus (VRE) but also against highly resistant Gram-negative organisms are more than welcome. Of these compounds some are already approved by official agencies, some are still in study, but the need of new antibiotics still does not cover the increasing prevalence of antibiotic-resistant bacterial infections. Therefore the management of antimicrobial resistance should also include fostering coordinated actions by all stakeholders, creating policy guidance, support for surveillance and technical assistance.